2013
DOI: 10.1007/s00428-013-1417-1
|View full text |Cite
|
Sign up to set email alerts
|

Clonality analysis suggests that STK11 gene mutations are involved in progression of lobular endocervical glandular hyperplasia (LEGH) to minimal deviation adenocarcinoma (MDA)

Abstract: Lobular endocervical glandular hyperplasia (LEGH) is a benign proliferative disease of cervical glands. Although histological resemblance of minimal deviation adenocarcinoma (MDA) to LEGH and frequent association of LEGH with MDA have been reported, it still remains unclear whether LEGH is a precancerous lesion of MDA. The present study was undertaken to examine the pathogenetic relationship between LEGH and MDA using a clonality analysis and mutational analyses of the STK11 gene, of which mutations have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…Kuragaki et al reported that 55% of MDA cases had a mutation in the STK11 gene 32. We also reported that STK11 may be involved in the progression of LEGH to MDA, according to a case containing mixed lesion of LEGH and MDA with the same clonality, whereas STK11 gene mutation was observed only in MDA lesion 12. In the present study, GNAS gene mutations were detected in two (14.3%) out of 14 cases of LEGH.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Kuragaki et al reported that 55% of MDA cases had a mutation in the STK11 gene 32. We also reported that STK11 may be involved in the progression of LEGH to MDA, according to a case containing mixed lesion of LEGH and MDA with the same clonality, whereas STK11 gene mutation was observed only in MDA lesion 12. In the present study, GNAS gene mutations were detected in two (14.3%) out of 14 cases of LEGH.…”
Section: Discussionsupporting
confidence: 57%
“…Although LEGH was first reported as a benign disease, it has been reported as a precursor of MDA, because of frequent association between LEGH and MDA as well as its genetic characteristics 6, 7, 8, 9, 10, 11. We previously reported that some LEGH lesions were a precancerous form of MDA due to the pattern of X chromosome inactivation using the human androgen receptor (HUMARA) method 12. Therefore, the possibility of a focal association with carcinoma in LEGH needs to be considered in its management.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have identified gene mutations that suggest MDA is an evolutionary lesion due to LEGH progression 15. Gastric-type adenocarcinomas are present in the upper endocervix as a bulky cervix, are typically p16 negative, demonstrate gastric differentiation in immunohistochemical reactions, and may be associated with LEGH, the putative precursor 5 11…”
Section: Discussionmentioning
confidence: 99%
“…As it is known that MDA complicates PJS, and LEGH has been suggested to be a precursor of MDA and adenocarcinoma, hysterectomy was also considered for our patient. Lesions of LEGH and MDA tend to be present near the internal os, rather than the squamocolumnar junction .…”
Section: Discussionmentioning
confidence: 99%